Effect of Non-Performing Loan and Bi Rate on The Credit Amount of Msme: A Case Study of Soe Banking Companies - Adhis Darussalam Pamungkas (Peneliti.net, 2020)
This research was conducted with the aim to better understand whether there are variables and how much the variables of Non Performing Loans (NPL) and BI Rate that affect the amount of MSME Credit distributed by the Persero in the 2014-2018 observation period. The population used in this research was the financial statements of SOE banking companies that belonged to as many as 4 banks consisting PT. Bank Negara Indonesia Tbk, PT. Bank Rakyat Indonesia Tbk, PT. Bank Mandiri Tbk, and PT. Bank Tabungan Negara Tbk. Sampling was carried out using the purposive sampling method, the data used came from the OJK annual report and the financial statements attached to the websites of each state-owned bank during 2014-2018. The methods used include multiple linear regression analysis, coefficient of determination, f test (simultaneous test), and t test (partial test). The results of this study indicate that NPL partially has a significant effect on the number of MSME loans. While the BI Rate partially has no significant effect on the number of MSME loans. Then from the results of the F test it was concluded that the NPL and BI Rate had a simultaneous effect on the number of MSME loans.